(untitled) (Sociologisk Forskning, 2015)
Enacting the apocalypse: zombie metaphors in contemporary disaster preparedness Since the turn of the millennium, enactment of possible emergencies and catastrophes has become a most common way of producing knowledge about events yet to occur. Preparedness exercises are frequently performed by public authorities at local and regional levels. Collaborative approaches among relevant actors are enhanced and evaluated through simulated accidents and acts of terror as well as school shootings and epidemic outbreaks. Due to the incalculability of many modern threats, enactment is employed as a method for rendering potential future events available as empirical phenomena. However, sometimes these potential futures are represented in ways that correspond only to imagined and fictional worlds. The aim of this article is to explore the enactment of unreal possibilities in contemporary preparedness exercises. The empirical material employed for this purpose consists of crisis plans and exercise guides used in public and official institutions in the United States as well as qualitative interviews with municipal safety coordinators in Sweden.